One-pot synthesis of diaryliodonium salts from arenes and aryl iodides with Oxone–sulfuric acid - Soldatova, Natalia; Postnikov, Pavel; Kukurina, Olga; Zhdankin, Viktor V.; Yoshimura, Akira; Wirth, Thomas; Yusubov, Mekhman S. (Beilstein Journal of Organic Chemistry, 2018)
A facile synthesis of diaryliodonium salts utilizing Oxone as versatile and cheap oxidant has been developed. This method shows wide applicability and can be used for the preparation of iodonium salts containing electron-donating or electron-withdrawing groups in good yields. In addition, this procedure can be applied to the preparation of symmetric iodonium salts directly from arenes via a one-pot iodination–oxidation sequence.
Keywords: diaryliodonium salts; iodine; iodonium; oxidation; Oxone

(untitled) - Yusubov, M. S.; Maskaev, A. V.; Zhdankin, V. V. (ARKIVOC, 2011)

Hypervalent Iodine Chemistry - Zhdankin, V. V. (Wiley, 2014)

(untitled) - Yoshimura, A.; Zhdankin, V. V. (Chem. Rev., 2016)

Hypervalent Iodine Chemistry in Topics in Current Chemistry - Wirth, T. (Springer, 2016)

(untitled) - Merritt, E. A.; Olofsson, B. (Angew. Chem., Int. Ed., 2009)

(untitled) - Aradi, K.; Tóth, B. L.; Tolnai, G. L.; Novák, Z. (Synlett, 2016)

(untitled) - Fañanás-Mastral, M. (Synthesis, 2017)

(untitled) - Gonda, Z.; Novák, Z. (Chem. – Eur. J., 2015)

(untitled) - Dey, C.; Lindstedt, E.; Olofsson, B. (Org. Lett., 2015)

(untitled) - Tinnis, F.; Stridfeldt, E.; Lundberg, H.; Adolfsson, H.; Olofsson, B. (Org. Lett., 2015)

(untitled) - Cahard, E.; Male, H. P. J.; Tissot, M.; Gaunt, M. J. (J. Am. Chem. Soc., 2015)

(untitled) - Modha, S. G.; Greaney, M. F. (J. Am. Chem. Soc., 2015)

(untitled) - Beaud, R.; Phipps, R. J.; Gaunt, M. J. (J. Am. Chem. Soc., 2016)

(untitled) - Yin, K.; Zhang, R. (Org. Lett., 2017)

(untitled) - Seidl, T. L.; Stuart, D. R. (J. Org. Chem., 2017)

(untitled) - Margida, A. J.; Koser, G. F. (J. Org. Chem., 1984)

(untitled) - Kitamura, T.; Matsuyuki, J.-i.; Nagata, K.; Furuki, R.; Taniguchi, H. (Synthesis, 1992)

(untitled) - Kitamura, T.; Matsuyuki, J.-i.; Taniguchi, H. (Synthesis, 1994)

(untitled) - Pike, V. W.; Butt, F.; Shah, A.; Widdowson, D. A. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Carroll, M. A.; Pike, V. W.; Widdowson, D. A. (Tetrahedron Lett., 2000)

(untitled) - Kaźmierczak, P.; Skulski, L. (Synthesis, 1995)

(untitled) - Kryska, A.; Skulski, L. (Molecules, 2001)

(untitled) - Hossain, M. D.; Kitamura, T. (Tetrahedron, 2006)

(untitled) - Hossain, M. D.; Ikegami, Y.; Kitamura, T. (J. Org. Chem., 2006)

(untitled) - Dohi, T.; Yamaoka, N.; Itani, I.; Kita, Y. (Aust. J. Chem., 2011)

(untitled) - Bielawski, M.; Zhu, M.; Olofsson, B. (Adv. Synth. Catal., 2007)

(untitled) - Bielawski, M.; Olofsson, B. (Chem. Commun., 2007)

(untitled) - Bielawski, M.; Aili, D.; Olofsson, B. (J. Org. Chem., 2008)

(untitled) - Zhu, M.; Jalalian, N.; Olofsson, B. (Synlett, 2008)

(untitled) - Jalalian, N.; Olofsson, B. (Tetrahedron, 2010)

(untitled) - Seidl, T. L.; Sundalam, S. K.; McCullough, B.; Stuart, D. R. (J. Org. Chem., 2016)

(untitled) - Lindstedt, E.; Reitti, M.; Olofsson, B. (J. Org. Chem., 2017)

(untitled) - Carreras, V.; Sandtorv, A. H.; Stuart, D. R. (J. Org. Chem., 2017)

(untitled) - Gemoets, H. P. L.; Laudadio, G.; Verstraete, K.; Hessel, V.; Noël, T. (Angew. Chem., Int. Ed., 2017)

(untitled) - Laudadio, G.; Gemoets, H. P. L.; Hessel, V.; Noël, T. (J. Org. Chem., 2017)

(untitled) - Frigerio, M.; Santagostino, M.; Sputore, S. (J. Org. Chem., 1999)

(untitled) - Yusubov, M. S.; Yusubova, R. Y.; Nemykin, V. N.; Zhdankin, V. V. (J. Org. Chem., 2013)

(untitled) - Yusubov, M. S.; Soldatova, N. S.; Postnikov, P. S.; Valiev, R. R.; Svitich, D. Y.; Yusubova, R. Y.; Yoshimura, A.; Wirth, T.; Zhdankin, V. V. (Eur. J. Org. Chem., 2018)

(untitled) - Postnikov, P. S.; Guselnikova, O. A.; Yusubov, M. S.; Yoshimura, A.; Nemykin, V. N.; Zhdankin, V. V. (J. Org. Chem., 2015)

(untitled) - Zagulyaeva, A. A.; Yusubov, M. S.; Zhdankin, V. V. (J. Org. Chem., 2010)

(untitled) - Soldatova, N.; Postnikov, P.; Troyan, A. A.; Yoshimura, A.; Yusubov, M. S.; Zhdankin, V. V. (Tetrahedron Lett., 2016)

(untitled) - Soldatova, N. S.; Postnikov, P. S.; Kukurina, O. S.; Zhdankin, V. V.; Yoshimura, A.; Wirth, T.; Yusubov, M. S. (ChemistryOpen, 2017)

(untitled) - Yakura, T.; Omoto, M.; Yamauchi, Y.; Tian, Y.; Ozono, A. (Tetrahedron, 2010)